1996
DOI: 10.1017/s0272263100015394
|View full text |Cite
|
Sign up to set email alerts
|

Explanation versus Structured Input in Processing Instruction

Abstract: This study replicates VanPatten and Cadierno (1993) in an attempt to determine whether or not explicit information given to learners receiving processing instruction is responsible for the beneficial effects of instruction. Fifty-nine subjects were divided into three groups: (1) one receiving processing instruction in object pronouns and word order in Spanish as in VanPatten and Cadierno (1993), (2) another receiving explanation only with no activities or practice, (3) and another receiving only the structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
180
2
10

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(210 citation statements)
references
References 10 publications
18
180
2
10
Order By: Relevance
“…Supporting the results of VanPatten and Cadierno's (1993) study, this finding suggests that PI as a direct intervention, as in VanPatten's model, can provide a way for "better processing of input and knowledge that is apparently also available for production" (VanPatten & Cadierno, 1993, p. 54) and an "opportunity to interpret the meaning-form relationship correctly without any practice in producing the targeted form or structure" (Lee & Benati, 2009, p. 75). In other words, as in the earlier studies (e.g., VanPatten & Oikkenon, 1996, among many others), when PI conditions with and without EI were compared on the production task, they performed equally well over time. That is, it was the structured input that helped learners to produce the targeted form, not the EI.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Supporting the results of VanPatten and Cadierno's (1993) study, this finding suggests that PI as a direct intervention, as in VanPatten's model, can provide a way for "better processing of input and knowledge that is apparently also available for production" (VanPatten & Cadierno, 1993, p. 54) and an "opportunity to interpret the meaning-form relationship correctly without any practice in producing the targeted form or structure" (Lee & Benati, 2009, p. 75). In other words, as in the earlier studies (e.g., VanPatten & Oikkenon, 1996, among many others), when PI conditions with and without EI were compared on the production task, they performed equally well over time. That is, it was the structured input that helped learners to produce the targeted form, not the EI.…”
Section: Discussionsupporting
confidence: 70%
“…All these studies found different results from those of VanPatten and Oikkenon (1996); that is, they reported a superior effect of the PI+EI group over PI-EI, thereby revealing a significant effect for EI, as well as that of structured input, in PI. In these studies, EI was found to play a facilitative role in PI, and therefore it was suggested to be beneficial in PI for different language features; this, however, depends on the nature of the tasks and the associated processing problem (Farley, 2004a;Fernandez, 2008;Henry et al, 2009).…”
Section: Processing Instruction and Explicit Informationmentioning
confidence: 83%
See 2 more Smart Citations
“…Further interconnectedness was found in two lines of research. First, Ellis and Sagarra (2011) served both as an initial study for the Ellis et al (2014) replication and was itself a replication of Ellis and Sagarra (2010), and thus it was coded as both a replication and an initial study; and second, VanPatten and Cadierno (1993a) served as an initial study for DeKeyser and Sokalski (1996) and for VanPatten and Oikkenon (1996), and so it was coded twice in its capacity as an initial study. Overall, though, the interconnectedness of groups of studies was minimal, given that from the 67 self-labeled replications, only four were associated with more than one initial study, only one continuing line of replications was identified, and only one study was replicated more than once.…”
Section: Have Closely Interconnected Series Of Initial and Replicatiomentioning
confidence: 99%